World economic policy—what's it all about - Emil Küng (Intereconomics, 1978)
A world government does not seem to be indispensable for a world economic policy. The work of international agencies, as inter alia IMF, GATT, ILO, WHO, UN Economic and Social Council and World Bank, proves the contrary. Global tasks can in many instances be tackled through treaties and specialized organisations with appropriate mandates.
Keywords: 330; World Economy